Metodología de evaluación ex post - Medianero Burga, David (2010)
This article provides a synthesis of ex post evaluation methodology used by the author in the evaluation of the Second Social Investment Program Infrastructure and Poverty (hereinafter the Program), executed by the MEF, with financial support from the Corporación Andina de Fomento (CAF). The aim of this action was to assess the levels of relevance, effectiveness, efficiency, impact and sustainability of public investment projects making up the program. To this end, the methodological framework adopted took into consideration that the object of an evaluation is to determine if the projects generate the desired effects on individuals and institutions which are run in accordance with the guidelines established in the pre-investment documents and appraisal approved by the official agencies. In general, the methodology used in this evaluation is oriented to draw valid conclusions about the performance of projects with regard to the criteria of relevance, effectiveness, efficiency, sustainability and impact. This methodology may be replicated in similar situations, that is why this brief summary is provided.